The Rise of Accounting Administration and Its Impact on the Profitability of Microeconomic Management - R. Acosta Velarde; M. Campaña Lara; E. Melendres Medina; J. Flores Dávila (ESPOCH Congresses)
Some taxes may limit microeconomic growth. A greater growth of SMEs that use RISE as part of their administration, especially grocery stores, has been identified in the commercial sector in the city of Macas, Morona canton, Morona Santiago province, Ecuador. This has led to a lack of knowledge about their profitability because the nature of the tax can lead to reduced use of accounting tools. Therefore, the objective of this research was to analyze the accounting administration of RISE and its impact on the profitability of these businesses, and to propose the design of a tool that could contribute to the development of efficient management of the local microeconomic businesses. A deductive quantitative approach was used and data were collected through a survey and interviews. The Chi square test was used to analyze the results. According to the findings, the limitations faced by businesses that use this tax included the generation of monthly income that does not cover the monthly basic basket. Based on the results, we proposed a strategy for the efficient management of the microeconomy that is made up of four tools: conscious strategic planning, administration without tax barriers, efficient accounting tools, and the sustainable development of the company.